El uso de la leyenda del açaí como herramienta para el desarrollo de la escrita en e/le para alumnos del 9º año en la escuela Leonidas Montes en Abaetetuba-PA - QUARESMA, Juliete Brandão da Costa (2019)
The article has like objective develop the skills written in E / LE through the use of the legends of Acai with students grad 9 at the Leonidas Monte school in Abaetetuba, Pará. We propose a didactic sequence based on Dolz, Noverraz and Schneuwly (2004). Applied in two classes of E / LE. In addition, we did a bibliographical review, we had as a theoretical basis the perspective of Cassany (1993, 1999, 2009), Sánchez (2009) and Giovannini (1996) as well as reading researchers in classes or teaching through genres textual. As methodology, we conducted a qualitative research, more specifically a field study, through the application of the didactic sequence and questionnaires for the teacher and students of the class. The results of the research reveal that the teacher recognizes the importance of the use of legend in learning E / LE, however, it was verified that the same approaches in its classes in the dates commemorative of the folklore. From the perspective of the students it was possible to verify that the result was significant, as the use of Acai legend in class contributed to the development of writing and promoted the production of learning skills written in Spanish.